Walter Pater: humanist. - Crinkley, Richmond, 1940-1989 (1970)
This provocative study suggests that Pater, usually thought of as a florid prose stylist and second-rate adjunct to the Esthetic Movement, is, in reality, an articulate prophet of the twentieth century. Pater's work, the book indicates, shows a consistent concern with the transmission of humanism from one generation to the next through the medium of art. The link in that transmission is the human image in a milieu -- the appearance of man as manifested in painting, sculpture, prose, poetry, or drama. Pater's fiction, as well as his criticism, strives to create a milieu, extracting both what is unique and what is constant from that milieu. His treatment of humanism has seemed introverted, bizarre, almost obsessional, but he prefigured the concerns of such writers as Joyce and Yeats, and his esthetic has become an accepted part of our mid-twentieth century intellectual structure.
Keywords: Pater, Walter, -- 1839-1894 -- Criticism and interpretation.; Pater, Walter, -- 1839-1894 -- Critique et interprétation.; Pater, Walter, -- 1839-1894; Pater, Walter (Schriftsteller); Humanism in literature.; Humanisme dans la littérature.; LITERARY COLLECTIONS -- Essays.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Humanism in literature; Criticism, interpretation, etc.